2019
DOI: 10.1186/s12888-019-2322-1
|View full text |Cite
|
Sign up to set email alerts
|

Sense it and use it: interoceptive accuracy and sensibility in suicide ideators

Abstract: BackgroundInteroceptive deficits have been found to be associated with suicidal ideation and behavior. However, an objective measure of interoceptive accuracy has not been investigated in participants with suicide ideation, by now. This study aimed at investigating interoceptive accuracy and sensibility in persons with and without suicide ideation (SI) while controlling for severity of depressive symptoms.MethodNinety-five participants (age: M = 34.8, SD = 11.6, n = 56 female [58.9%]; n = 51 patients with a Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 40 publications
2
13
0
Order By: Relevance
“…Prior to treatment, inter-scale correlations were largely comparable with the English MAIA-2 validation study [ 35 ] except for Noticing and Not-Worrying showing a moderately negative correlation at admission, but not at discharge (Mehling et al [ 35 ]: r = -.09). To the best of our knowledge, there is only one previous study recruiting depressed patients and reporting scale-scale correlations which found no significant correlation between both scales [ 68 ]. However, Forkmann et al used the original MAIA, which may limit the comparability of the results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to treatment, inter-scale correlations were largely comparable with the English MAIA-2 validation study [ 35 ] except for Noticing and Not-Worrying showing a moderately negative correlation at admission, but not at discharge (Mehling et al [ 35 ]: r = -.09). To the best of our knowledge, there is only one previous study recruiting depressed patients and reporting scale-scale correlations which found no significant correlation between both scales [ 68 ]. However, Forkmann et al used the original MAIA, which may limit the comparability of the results.…”
Section: Discussionmentioning
confidence: 99%
“…A possible link between interoception and intensified self-focus in depression may be of great clinical interest [ 16 ] as shifts to maladaptive self-referential cognitive styles predict prolonged episode duration [ 70 ] and play a major role in the onset of future depression [ 71 ]. It has also been shown that worry about physical sensations may be associated with increased suicidal ideation [ 68 , 72 ]. Conversely, post-treatment scores revealed a moderate positive correlation between Not-Worrying and Trusting, which was not found at admission, but may be indicative of an interrelatedness of both constructs in the post-treatment period.…”
Section: Discussionmentioning
confidence: 99%
“…Disrupted interoception—an impaired ability to accurately perceive the emotional and physiological condition of the entire body (Craig, 2002)—may be necessary for self‐injurious behaviors (SIBs), including NSSI, to occur (Forrest et al, 2015; Franklin et al, 2012; Muehlenkamp, 2012; Rogers et al, 2018; Ross et al, 2009). Interoception is a multifaceted construct (Garfinkel et al, 2015; Khalsa et al, 2018), yet most prior research examining the relation between interoception and SIBs has measured only interoceptive sensibility, which is assessed via self‐report measures (though see DeVille et al, 2020; Forkmann et al, 2019; Young et al, 2019). To more fully examine the extent and modes of interoception that may be dysregulated in people with SIBs, multiple domains of interoceptive processing must be considered (Garfinkel et al, 2015; Khalsa et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Anxiety has been also associated with reduced interoceptive abilities 6 , 35 38 , and interoceptive training seems to reduced anxiety scores in healthy volunteers 39 . Also, depression is usually characterized by interoceptive impairments and poor interoceptive accuracy 35 , 38 , 40 , 41 . It is likely that both temporal and spatial locations of heartbeat sensations may be affected in these clinical and subclinical groups 6 , 8 , 23 , 28 , 35 , but such relationships have never been tested to date.…”
Section: Introductionmentioning
confidence: 99%